Avaliação do efeito antinociceptivo periférico do sulfato de magnésio em camundongos - Loyara Rocha Miranda Teixeira (2019)
Magnesium plays a fundamental role in many biological functions, and thus there is increasing interest in clinical medicine. In addition, the analgesic functions have been shown in models of acute and chronic pain, as well as in animals and clinical practice. However, mechanisms of action remain unknown. The aim of this study is to verify effect and antinociceptive mechanisms of magnesium sulphate administered locally into the hindpaw. The male swiss mice paw pressure test was used, according described by Randall & Sellito. In our experiments, hyperalgesia was induced by subcutaneous injection of prostaglandin E2 (PGE2: 2 μg/paw), calcium ionophore, calcimycin (A23187: 20 µg/paw) and agonist of N-methyl-D-aspartate glutamate receptor (NMDA: 12 µg/paw) into the plantar surface of the hindpaw. Magnesium sulphate injected into the right hind paw (20, 40, 80 e 160 µg/paw) induced antinociceptive effect in a dose-dependent manner. The dose of 80 µg per paw was able to reverse the hyperalgesia induced by PGE2 almost completely without systemic effects, in comparison to vehicle (NaCl 0,9%). However, a dose of 40 µg per paw induced partial antinoception, as a dose of 160 µg per paw produced antinociception in the opposite paw. We have tested whether the NO/cGMP/K+ATP pathway plays an important role in this process. The antinociceptive effect of MgSO4 (80 µg/paw) was antagonized by the non-selective NOS inhibitor (L-NOArg: 12, 18 and 24 µg/paw), the selective neuronal NOS inhibitor (L-NPA: 12, 18, and 24 µg/paw) and the soluble guanylyl cyclase inhibitor (ODQ: 25, 50, and 100 µg/paw) in a dose dependent manner. Endothelial (eNOS) and inducible (iNOS) selective NOS inhibitors (L-NIO: 24 g/paw and L-NIL: 24 µg/paw, respectively) were not able to block the antinociceptive effect. The cGMP-phosphodiesterase inhibitor (zaprinast:50 µg/paw) enhanced the antinociceptive effects of low-dose MgSO4 (40 µg/paw). The K+ATP specific blocker (glibenclamide: 20, 40 and 80 µg/paw) antagonized magnesium sulphate-induced peripheral antinociception (80 µg/paw) in a dose dependent manner. In another experiment, the nonselective voltage-dependent K+ channel blocker (tetraethylammonium: 30 µg/paw) and small and large conductance blockers of Ca2+-activated K+ channels (dequalinium: 50 µg/paw and paxilline: 20 µg/paw, respectively) were ineffective at blocking the effect of a local MgSO4 injection. The non-selective opioids receptors antagonist (naloxone: 50 g/paw), as well as the CB1-selective cannabinoid receptor antagonist (AM251: 160g/paw) and the CB2-selective cannabinoid receptor antagonist (AM630: 100 g/paw), did not reverse the analgesic effects of magnesium sulphate. The hyperalgesia induced by calcimycin and NMDA was also reversed by MgSO4 80µg/paw. Our results suggest that magnesium sulphate induce peripheral antinociceptive effects in the PGE2 induced inflammatory pain model by the NO/cGMP/K+ATP pathway activation. At the same way, MgSO4 also reverse the hyperalgesia induced by calcimycin and NMDA, suggesting calcium and glutamate NMDA receptor antagonism might be additional analgesic mechanisms.